2020
DOI: 10.1093/ckj/sfaa198
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors for non-diabetic kidney disease: drugs to treat CKD that also improve glycaemia

Abstract: Sodium–glucose co-transporter-2 (SGLT2) inhibitors decreased cardiovascular (CV) events and improved renal outcomes in CV safety studies in type 2 diabetes melitus (T2DM) patients at high CV risk. Canagliflozin also improved kidney outcomes in diabetic kidney disease in the Canagliflozin and Renal Events in Diabetes and Nephropathy Clinical Evaluationtrial. More recently, the Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure (DAPA-HF) trial showed that dapagliflozin improved CV outcomes in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 24 publications
1
52
0
5
Order By: Relevance
“…Dapagliflozin reduced significantly the risk of the primary combined endpoint of >50% eGFR decline, onset of ESKD or kidney or CV death with a hazard ratio of 0.61 (95% CI 0.51-0.72). 76 The renal benefits were comparable in patients with diabetic and non-diabetic kidney diseases. The impact on cardiac events and mortality were also significant.…”
Section: New Therapies To Lower Bp In Hypertensionmentioning
confidence: 98%
“…Dapagliflozin reduced significantly the risk of the primary combined endpoint of >50% eGFR decline, onset of ESKD or kidney or CV death with a hazard ratio of 0.61 (95% CI 0.51-0.72). 76 The renal benefits were comparable in patients with diabetic and non-diabetic kidney diseases. The impact on cardiac events and mortality were also significant.…”
Section: New Therapies To Lower Bp In Hypertensionmentioning
confidence: 98%
“…Large randomized controlled trials in diabetic and non-diabetic patients with CKD and HF have shown that SGLT2 inhibitors can slow kidney dis-ease progression, reduce cardiovascular events, and improve survival independently of the presence of diabetes [136]. Moreover, their potential use in several IR associated disorders, to improve current clinical management and ameliorate the increased cardiovascular burden, is evolving [2,3,17,137].…”
Section: Discussionmentioning
confidence: 99%
“…This may be based on simple lifestyle changes (exercise, diet, stop smoking) or be further supported, once the diagnoses were confirmed, by drug therapy. Renin-angiotensin system blockade and metformin represent low cost and effective drugs for hypertension, kidney protection, diabetes treatment and weight loss ( Fernandez-Fernandez et al, 2020 ). While SGLT2 inhibitors are yet expensive, the cost is expected to significantly come down in the near future, providing additional drugs that treat type 2 diabetes while promoting weight loss, a lowering blood pressure and affording kidney and cardiac protection ( Fernandez-Fernandez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%